Nanostructured surfaces by supramolecular self-assembly of linear oligosilsesquioxanes with biocompatible side groups - Nowacka, Maria; Kowalewska, Anna; Makowski, Tomasz (Beilstein Journal of Nanotechnology, 2015)
Linear oligomeric silsesquioxanes with polar side moieties (e.g., carboxylic groups and derivatives of N-acetylcysteine, cysteine hydrochloride or glutathione) can form specific, self-assembled nanostructures when deposited on mica by dip coating. The mechanism of adsorption is based on molecule-to-substrate interactions between carboxylic groups and mica. Intermolecular cross-linking by hydrogen bonds was also observed due to the donor–acceptor character of the functional groups. The texture of supramolecular nanostructures formed by the studied materials on mica was analysed with atomic force microscopy and their specific surface energy was estimated by contact angle measurements. Significant differences in the surface roughness, thickness and the arrangement of macromolecules were noted depending on the kind of functional groups on the side chains. Specific changes in the morphology of the surface layer were observed when mica was primed with a monolayer of small organic compounds (e.g., N-acetylcysteine, citric acid, thioglycolic or acid). The adsorption of both silsesquioxane oligomers and organic primers was confirmed with attenuated total reflectance infrared spectroscopy. The observed physiochemical and textural variations in the adsorbed materials correlate with the differences in the chemical structure of the applied oligomers and primers.
Keywords: atomic force microscopy; hydrophilicity; oligosilsesquioxanes; self-assembly; surface

(untitled) - Somorjai, G. A.; Li, Y. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Hudalla, G. A.; Murphy, W. L. (Soft Matter, 2011)

(untitled) - Arima, Y.; Iwata, H. (Biomaterials, 2007)

(untitled) - Palacio, M. L. B.; Bhushan, B. (Philos. Trans. R. Soc., A, 2012)

(untitled) - Drelich, J.; Chibowski, E.; Meng, D. D.; Terpilowski, K. (Soft Matter, 2011)

(untitled) - Azimi, G.; Dhiman, R.; Kwon, H.-M.; Paxson, A. T.; Varanasi, K. K. (Nat. Mater., 2013)

(untitled) - Yilgor, I.; Bilgin, S.; Isik, M.; Yilgor, E. (Langmuir, 2012)

(untitled) - Mendes, P. M. (Chem. Soc. Rev., 2008)

(untitled) - Liu, X.; Wang, S. (Chem. Soc. Rev., 2014)

(untitled) - Higuchi, A.; Ling, Q.-D.; Chang, Y.; Hsu, S.-T.; Umezawa, A. (Chem. Rev., 2013)

(untitled) - Rashidi, H.; Yang, J.; Shakesheff, K. M. (Biomater. Sci., 2014)

(untitled) - Li, D.; Zheng, Q.; Wang, Y.; Chen, H. (Polym. Chem., 2014)

(untitled) - Schaap-Oziemlak, A. M.; Kühn, P. T.; van Kooten, T. G.; van Rijn, P. (RSC Adv., 2014)

(untitled) - Faucheux, N.; Schweiss, R.; Lützow, K.; Werner, C.; Groth, T. (Biomaterials, 2004)

(untitled) - Curran, J. M.; Chen, R.; Hunt, J. A. (Biomaterials, 2006)

(untitled) - Ren, Y.-J.; Zhang, H.; Huang, H.; Wang, X.-M.; Zhou, Z.-Y.; Cui, F.-Z.; An, Y.-H. (Biomaterials, 2009)

(untitled) - Lee, J. H.; Jung, H. W.; Kang, I.-K.; Lee, H. B. (Biomaterials, 1994)

(untitled) - Lee, J. H.; Khang, G.; Lee, J. W.; Lee, H. B. (J. Colloid Interface Sci., 1998)

(untitled) - Tamada, Y.; Ikada, Y. (J. Colloid Interface Sci., 1993)

(untitled) - Rodríguez Patino, J. M.; Rodríguez Niño, M. R.; Carrera Sánchez, C. (Curr. Opin. Colloid Interface Sci., 2007)

(untitled) - Zhai, J. L.; Day, L.; Aguilar, M.-I.; Wooster, T. J. (Curr. Opin. Colloid Interface Sci., 2013)

(untitled) - Curran, J. M.; Chen, R.; Hunt, J. A. (Biomaterials, 2005)

(untitled) - Franco, M.; Nealey, P. F.; Campbell, S.; Teixeira, A. I.; Murphy, C. J. (J. Biomed. Mater. Res., Part A, 2000)

(untitled) - McClary, K. B.; Ugarova, T.; Grainger, D. W. (J. Biomed. Mater. Res., Part A, 2000)

(untitled) - Lan, M. A.; Gersbach, C. A.; Michael, K. E.; Keselowsky, B. G.; García, A. J. (Biomaterials, 2005)

(untitled) - Tidwell, C. D.; Ertel, S. I.; Ratner, B. D.; Tarasevich, B. J.; Atre, S.; Allara, D. L. (Langmuir, 1997)

(untitled) - Keselowsky, B. G.; Collard, D. M.; García, A. J. (Proc. Natl. Acad. Sci. U. S. A., 2005)

(untitled) - Lee, M. H.; Ducheyne, P.; Lynch, L.; Boettiger, D.; Composto, R. J. (Biomaterials, 2006)

(untitled) - Ulman, A. (Chem. Rev., 1996)

(untitled) - Marmisollé, W. A.; Capdevila, D. A.; de la Llave, E.; Williams, F. J.; Murgida, D. H. (Langmuir, 2009)

(untitled) - Park, J.-W.; Kim, H.; Han, M. (Chem. Soc. Rev., 2010)

(untitled) - Senaratne, W.; Andruzzi, L.; Ober, C. K. (Biomacromolecules, 2005)

(untitled) - Welch, M. E.; Ober, C. K. (J. Polym. Sci., Part B: Polym. Phys., 2013)

(untitled) - Love, J. C.; Estroff, L. A.; Kriebel, J. K.; Nuzzo, R. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Maroni, P.; Montes Ruiz-Cabello, F. J.; Cardoso, C.; Tiraferri, A. (Langmuir, 2015)

(untitled) - Kobayashi, M.; Terayama, Y.; Yamaguchi, H.; Terada, M.; Murakami, D.; Ishihara, K.; Takahara, A. (Langmuir, 2012)

(untitled) - Kowalewska, A.; Nowacka, M.; Tracz, A.; Makowski, T. (Soft Matter, 2015)

(untitled) - Liberelle, B.; Banquy, X.; Giasson, S. (Langmuir, 2008)

(untitled) - Leow, W. W.; Hwang, W. (Langmuir, 2011)

(untitled) - Loo, R. W.; Goh, M. C. (Langmuir, 2008)

Encyclopedia of Surface and Colloid Science - Rojas, O. J. (Adsorption of polyelectrolytes on mica, 2002)

(untitled) - Zhao, F.; Du, Y.-K.; Yang, P.; Tang, J.; Li, X.-C. (Colloid Polym. Sci., 2005)

(untitled) - Heredia-Guerrero, J. A.; San-Miguel, M. A.; Sansom, M. S. P.; Heredia, A.; Benítez, J. J. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Heredia-Guerrero, J. A.; San-Miguel, M. A.; Sansom, M. S. P.; Heredia, A.; Benítez, J. J. (Langmuir, 2009)

(untitled) - Benítez, J. J.; Heredia-Guerrero, J. A.; Serrano, F. M.; Heredia, A. (J. Phys. Chem. C, 2008)

(untitled) - Benítez, J. J.; Heredia-Guerrero, J. A.; Heredia, A. (J. Phys. Chem. C, 2007)

(untitled) - Chen, J.; Murphy, A. R.; Esteve, J.; Ogletree, D. F.; Salmeron, M.; Fréchet, J. M. J. (Langmuir, 2004)

(untitled) - Kowalewska, A.; Nowacka, M. (Silicon, 2015)

Adsorption from Solution at the Solid/Liquid Interface - Fleer, G. J.; Lyklema, J. (Academic Press, 1983)

(untitled) - Whitesides, G. M.; Mathias, J. P.; Seto, C. T. (Science, 1991)

(untitled) - Liu, L.; Guo, Q.-X. (Chem. Rev., 2001)

(untitled) - Linse, P.; Källrot, N. (Macromolecules, 2010)

(untitled) - Owens, D. K.; Wendt, R. C. (J. Appl. Polym. Sci., 1969)

Infrared Spectral Interpretation: A Systematic Approach - Smith, B. (CRC Press LLC, 1999)